2013
DOI: 10.1557/jmr.2013.30
|View full text |Cite
|
Sign up to set email alerts
|

Novel nanosample preparation with a helium ion microscope

Abstract: In this article, we present novel sample preparation methods using a helium ion microscope (HIM). We report the possibility of reshaping, at room temperature, thin metal lines on an electron-transparent membrane: A set of platinum bridges with standard geometry (300 Â 200 Â 15 nm) was modified at room temperature into different shapes using focused helium (He)-ion beam. Also the applicability of the HIM as a tool for precise modification of silicon (Si) and strontium titanate (SrTiO 3 ) lamellae is shown and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…These structures would have been impossible with Ga FIB milling. Rudneva et al have developed a heating stage allowing milling of nanoscale patterns in Si and Ti and demonstrated that unlike other methods, HIM milling did not affect the crystalline structure of the samples when heated to a high enough temperature, even at the edges of the mill [157].…”
Section: Milling/patterningmentioning
confidence: 99%
“…These structures would have been impossible with Ga FIB milling. Rudneva et al have developed a heating stage allowing milling of nanoscale patterns in Si and Ti and demonstrated that unlike other methods, HIM milling did not affect the crystalline structure of the samples when heated to a high enough temperature, even at the edges of the mill [157].…”
Section: Milling/patterningmentioning
confidence: 99%
“…This encourages out-diffusion of the implanted helium before it can accumulate and also promotes annealing of ion-induced defects. Techniques using an in situ MEMS-based heater [ 207 ] and localized in situ pulsed laser-based heating [ 208 ] have been developed. In the latter, Stanford et al showed that around 90% of the implanted helium can be driven out using the laser-assist process, and that peripheral damage when milling graphene on an SiO 2 substrate can also be mitigated.…”
Section: Reviewmentioning
confidence: 99%
“…3 The high depth-of-field of the He þ FIB due to the collimated nature of the beam also enables the milling of high aspect-ratio features. In recent years, the He þ milling characteristics of bulk materials such as Si, 18,35,36 Cu, 18 SiO 2 , and Au (Refs. 38-41) have been observed.…”
Section: A Helium Millingmentioning
confidence: 99%
“…44 A more ubiquitous method to mitigate subsurface damage in membrane and bulk materials has been accomplished by enhancing the diffusion of implanted He þ ions, substrate material vacancies, and substrate material interstitials, which were generated by the cascading collision events. Previously, a special substrate heater 36 was used to provide in situ thermal energy and reduce unwanted subsurface damage. However, bulk heating may be impractical for processing complex samples where diffusion of dopants, metallization, or barrier layers limit the sample temperature.…”
Section: -4 Stanford Et Almentioning
confidence: 99%